2008
DOI: 10.1071/is07034
|View full text |Cite
|
Sign up to set email alerts
|

Systematics and evolution of the Australian subterranean hydroporine diving beetles (Dytiscidae), with notes on Carabhydrus

Abstract: Calcrete aquifers of the Yilgarn area of Western Australia and the Ngalia Basin, Northern Territory, Australia are known to contain a rich invertebrate stygofauna, including the world’s most diverse assemblage of subterranean diving beetles. Here we determine the generic relationships of these subterranean diving beetle species in the tribe Hydroporini and assess their evolutionary origins. Phylogenetic analyses of 1642 base pairs of mitochondrial DNA (mtDNA), comprising segments of CO1, 16S rRNA, tRNAleu and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 15 publications
5
63
1
Order By: Relevance
“…All three localities are in a very small area and probably in the same calcrete body, although we know very little about the actual complexity of these habitats and some recent studies suggest that they are much patchier than previously suspected Guzik et al, 2008). A significant difference in size between these two closely related species is very characteristic of selective pressures associated with recent sympatric distribution, and it is well documented in this region for many sympatric sister species of diving beetles (Leys et al, 2003;Leys and Watts, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…All three localities are in a very small area and probably in the same calcrete body, although we know very little about the actual complexity of these habitats and some recent studies suggest that they are much patchier than previously suspected Guzik et al, 2008). A significant difference in size between these two closely related species is very characteristic of selective pressures associated with recent sympatric distribution, and it is well documented in this region for many sympatric sister species of diving beetles (Leys et al, 2003;Leys and Watts, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…In the Yilgarn and Pilbara regions a myriad of short-range endemic species, including both stygobitic (Taiti and Humphreys 2001;Leys et al 2003;Leys and Watts 2008;Page et al 2008;Guzik et al 2009;Bradford et al 2010) and troglobitic (Humphreys and Adams 2001;Harvey et al 2008) taxa have been identified. Much of this diversity is likely to have resulted from vicariance associated with the aridification of the Australian continent after the late Miocene (Byrne et al 2008), which led to biotic isolation of calcretes and other subterranean habitats (e.g.…”
Section: The Predicted Origins Of This Diversitymentioning
confidence: 99%
“…The major beetle families found in caves are ground beetles (Carabidae: Trechinae), followed by small carrion beetles (Cholevidae or Cholevinae within Leiodidae) and rove beetles (Staphylinidae) (Moldovan, 2005) with large distributions in the palearctic and nearctic ecozones. In addition, a large diversity of aquatic troglobiotic diving beetles (Dytiscidae) has been discovered in Australia (Faille et al, 2010;Leys and Watts, 2008;Leys et al, 2003;Ribera et al, 2010). The Coleoptera are thus an ideal study group to explore the breadth of cave-adaptive states.…”
Section: Introductionmentioning
confidence: 99%